2021
DOI: 10.1096/fj.202000373rrrr
|View full text |Cite
|
Sign up to set email alerts
|

SETD7 mediates the vascular invasion in articular cartilage and chondrocytes apoptosis in osteoarthriis

Abstract: The pathological characteristics of osteoarthritis are cartilage matrix degradation, chondrocytes apoptosis, and low‐grade inflammation of the joint. Recent studies have shown that blood vessels grow from the subchondral bone to the articular cartilage. However, the relationship among inflammation, angiogenesis, and chondrocyte apoptosis is still unclear. We found that chondrocytes could secrete chemokines and VEGF to promote the migration of vascular endothelial cells in response to TNF‐α stimulation. The inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…In search for factors preventing angiogenesis to use in cancer therapy the line between anti-invasive factors and anti-angiogenic factor became blurred and led to cartilage being commonly accepted as being anti-angiogenic. 1 , 6 - 8 , 10 - 12 , 29 - 32 We confirmed that cartilage explants are not invaded by blood vessels in the CAM assay and that a high salt extract of cartilage matrix inhibited blood vessel attraction. However, our results demonstrated that although not invaded, cartilage explants do attract vessels, indicating that its releasate is pro-angiogenic.…”
Section: Discussionsupporting
confidence: 67%
“…In search for factors preventing angiogenesis to use in cancer therapy the line between anti-invasive factors and anti-angiogenic factor became blurred and led to cartilage being commonly accepted as being anti-angiogenic. 1 , 6 - 8 , 10 - 12 , 29 - 32 We confirmed that cartilage explants are not invaded by blood vessels in the CAM assay and that a high salt extract of cartilage matrix inhibited blood vessel attraction. However, our results demonstrated that although not invaded, cartilage explants do attract vessels, indicating that its releasate is pro-angiogenic.…”
Section: Discussionsupporting
confidence: 67%
“…In previous studies, SETD7 was shown to be highly expressed in chondrocytes at 20 compared with 1% O 2 ( 13 , 49 ). The present study demonstrated that at 1% O 2 , decreased SETD7 expression leads to inhibition of Hippo signaling and an increase in YAP entering the nucleus.…”
Section: Discussionmentioning
confidence: 85%
“…The thermocycling conditions were set as follows: Initial denaturation for 30 sec at 95°C; followed by 40 cycles of 95°C for 5 sec, 60°C for 30 sec and 95°C for 5 sec; melting at 65°C for 60 sec and 97°C for 1 sec and cooling at 50°C for 30 sec. Relative mRNA expression of target genes was calculated using the 2 −ΔΔCq method ( 13 ). The experiments were performed in triplicate and repeated three times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, SETD7 expression is suppressed under hypoxic conditions ( Liu et al, 2015 ). Others have reported that SETD7 is a negative regulator of HIF-1α and downregulates HIF-1α target genes, such as GLUT1, LDHA, PGK1, EPO, PKM2 and VEGF, which are upregulated after SETD7 inhibition ( Li et al, 2021 ; Xiaoshi et al, 2021 ).…”
Section: Setd7-mediated Substrate Modifications and Their Role In Cancermentioning
confidence: 99%